THE EFFECT OF SOCIAL MEDIA USE LEVEL AND SLEEP QUALITY ON WORK PERFORMANCE AMONG UNIVERSITY EMPLOYEES - Berkhan TOPAKTAŞ (Rojan GÜMÜŞ, 2024)
It is important to determine the level of social media addiction in the working population and to determine its relationship with sleep quality, and how both variables affect the work performance of the employees. In this study, it was aimed to determine the effects of social media addiction levels and sleep quality of employees at Amasya University on their work performance. The population of the cross-sectional study consisted of staff in all employment types at Amasya University. Sociodemographic data form, Social Media Addiction Scale-Adult Form (SMAS-AF), Pittsburgh Sleep Quality Index (PSQI), and Work Role Functioning Questionnaire (WRFQ) were applied by face-to-face survey method between August 15 and October 15, 2022. A total of 148 individuals participated in the study. The total score on the SMAS-AF was 40.0 (20-84), the PSQI total score was 6.0 (1-15) and the WRFQ total score was 92.5 (6-100). The WRFQ was found to be lower in individuals with associate degrees or higher education, females, and academic staff (p=0.042; p=0.010 and p=0.008 respectively). The WRFQ total score indicated low, moderate, and negative significant correlations with the SMAS-AF and PSQI total scores (r= -0.333 and -0.344, respectively, p< 0.001). It was found that as the level of social media addiction increased and sleep quality deteriorated, work role functionality was negatively affected. A holistic approach, including behavioral problems, should be exhibited in the evaluation of work performance.